The Art of the Impossible: Dave Barrett and the NDP in Power, 1972-1975 - Homel, Gene (Labour / Le Travail, 2014)
The article reviews the book, "The Art of the Impossible: Dave Barrett and the NDP in Power, 1972-1975," by Geoff Meggs and Rod Mickleburgh.
Keywords: ART of the Impossible: Dave Barrett & the NDP in Power 1972-1975, The (Book); BRITISH Columbia -- Politics & government -- 20th century; MEGGS, Geoff; MICKLEBURGH, Rod; NEW Democratic Party (Political party : British Columbia) -- History -- 20th century; Nonfiction